Case Report: A Case of Caprine Arthritis Encephalitis in Dairy Goat Farms in South Korea - Son, Ga-In; Hong, Eui-Ju; Shin, Hyun-Jin (Frontiers in Veterinary Science, 2021)
One Saanen dairy goat (Capra aegagrus hircus) farm in Korea reported that some goats showed clinical signs such as arthritis, paralysis, swelling of the carpal joints and even death. We monitored clinical signs and pathological lesions. In laboratory, we confirmed Caprine Arthritis Encephalitis Virus (CAEV) infection by Polymerase Chain Reaction (PCR). We examined all the dairy goat in a farm and found many of them were positive. In conclusion, CAEV infection outbreaks seem to spread rapidly to all goats on a farm, so CAEV infection has a serious economic impact. We need to regularly investigate all dairy goat farms, and more importantly, inspection of the quarantine stage should be required before importation. Interestingly, we found all negative results in Korean native black goats (Capra hircus linnaeus).